Penyuluhan Melalui Media Tokoh Adat Bayan (WETUTELU) Terhadap Pengetahuan Ibu Balita Tentang Pesan Gizi Seimbang - Denda Swidari; Lalu Khairul Abdi; Yuli Laraeni; Abdul Salam (Poltekkes Kemenkes Mataram, 2020)
Background : Factors of education and knowledge mothers of toddlers can influence nutritional status. One effort to improve nutritional status is to increase knowledge about nutrition with nutrition counseling. Knowledge can be influenced by education, people who are highly educated will have broader knowledge and have openness to accept new things. While people with low education tend to have old thinking patterns and are less open to new things including a strong area of customs and traditional. One of the ways to influence the mindset of community with these condition is to use a communication facilitator who is believed to be a role model for the community. So, in this reseach the role of cultural figure was used, so that people receive more material. Objectives : Knowing the influence of educatuin by cultural figure on knowledge of mothers of toddlers about balance nutritional massages. Methods : This Research is pre-experimental study. Which allows testing of changes that occur after the intervention. This research design was used one grup pretest-posttest design. Results : there is an increase in knowledge in the form of difference in scores from pretest to posttest. Based on the result of the analysis using wilcoxon, the influence of education by cultural figure on the knowledge of mothers of toddlers about balance nutritional massages obtained p=0.00 atau p<0.05 meaning there is influence. Conclusion : There is the influence of education by cultural figure on knowledge of mothers of toddlers about balanced nutrition massages.